Self-efficacy in Patients with Multiple Sclerosis: A Model Test Study - Niloofar Hejazizadeh; Marzieh Pazokian; Malihe Nasiri (Mashhad University of Medical Sciences, 2020)
Background: Multiple Sclerosis (MS) is a common disease among youngsters and self-efficacy is a crucial factor in these patients. Various variables, including demographic characteristics and disease symptoms, affect self-efficacy. Therefore, it is necessary to assess the relationship between these factors using a clear and comprehensive model. Aim: this study aimed to investigate the self-efficacy model for MS patients. Method: This descriptive-correlational study was performed on 203 patients referring to the Iran MS Society. Data collection tools entailed Rigby Multiple Sclerosis Self-efficacy Scale, Krupp Fatigue Severity Scale, and Rosenberg Self-Esteem Scale. Data were analyzed by the SPSS 24 and LISREL 8.8. Results: The mean scores of self-efficacy, fatigue, and self-esteem were found as 39.6±9.1, 38.1±14.4, and 19±7.6, respectively. The model fit indices, including the goodness of fit index, comparative fit index, root mean square error of approximation, normalized fitness index, non-normalized fitness index, and the degree of freedom for the Chi-square were obtained as 0.9, 1, 0.002, 0.9, 0.9, and 1.03, respectively. Results indicated an appropriate prediction for the paths considered to determine the relationship between variables. Our findings demonstrated a significant correlation between self-efficacy and self-esteem (r=0.2), fatigue and self-esteem (r=-0.1) (P<0.001), as well as family support and self-esteem. Moreover, fatigue was observed to have a significant relationship with marital status, hospitalization, and exercise. However, no significant relationship was observed between fatigue and self-efficacy (r=0.02) (P>0.05). Implications for Practice: The results showed that the Bandura model of self-efficacy can be used for the demographic and clinical variables of MS patients. Findings of this study can be helpful in developing and implementing instructional plan to improve self-efficacy in these patients.